2013
DOI: 10.1614/wt-d-13-00001.1
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Reed-Sedge Peat Moss on Hybrid Bermudagrass Injury with Indaziflam and Prodiamine in Sand-Based Root Zones

Abstract: PRE herbicides have been reported to injure both the foliage and roots of hybrid bermudagrass turf established in sand culture. Research was conducted to evaluate the influence of reed-sedge peat moss (RSPM) on hybrid bermudagrass injury following PRE herbicide applications to plants established in sand culture. Washed sod plugs were established in mini-rhizotrons constructed with sand root-zones varying in organic carbon content (0.000, 0.003, 0.007, and 0.012 kg kg−1). Herbicide treatments included indazifla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
10
0
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 18 publications
4
10
0
2
Order By: Relevance
“…The influence of net negatively charged clay minerals and pH on the CEC could be responsible for the repulsion of indaziflam from sorption sites. A study conducted by [ 5 ] showed an increase in CEC with increasing organic matter that at the same time reduced the toxicity of indaziflam to hybrid bermudagrass in sand cultures. The CEC of organic matter increases with soil pH, however, the sorption of indaziflam to organic matter could be due to the triazine amide group of indaziflam [ 5 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The influence of net negatively charged clay minerals and pH on the CEC could be responsible for the repulsion of indaziflam from sorption sites. A study conducted by [ 5 ] showed an increase in CEC with increasing organic matter that at the same time reduced the toxicity of indaziflam to hybrid bermudagrass in sand cultures. The CEC of organic matter increases with soil pH, however, the sorption of indaziflam to organic matter could be due to the triazine amide group of indaziflam [ 5 ].…”
Section: Resultsmentioning
confidence: 99%
“…Batch experiments indicated that indaziflam is low to moderately mobile in the soil and its sorption was positively correlated with the organic carbon content in six Brazilian oxisols and three U.S. mollisols [ 1 ]. Jones et al [ 5 ] evaluated the effect of organic matter content on hybrid bermudagrass ( Cynodon dactylon x Cynodon transvaalensis ) injury following the application of indaziflam in minirhizotron cultures. Hybrid bermudagrass injuries decreased with increasing organic matter content.…”
Section: Introductionmentioning
confidence: 99%
“…Studies conducted on indaziflam found that sorption in soil was positively correlated to soil organic carbon ranging from 0.5 to 2.5% and clay content ranging from 7 to 65% (Alonso et al, 2011). Jones et al (2013b) found that adding peat moss to sand at a rate of 40% by volume reduced hybrid bermudagrass injury by 77% at 6 WAT following 52.5 g ha −1 indaziflam, compared with plants grown in pure sand. The bioavailability and, therefore, the potential phytotoxicity of indaziflam may be reduced in soils with greater clay content or OM.…”
mentioning
confidence: 97%
“…Apesar das baixas doses de aplicação, este apresenta uma longa atividade residual para a maioria dos usos propostos, como resultado da sua longa persistência no solo (U.S. EPA, 2010). Segundo Jones et al (2013), o aumento no teor de carbono orgânico do solo promove redução nas lesões foliares e radiculares de híbridos de grama-bermuda (Cynodon dactylon) expostos ao indaziflam. Este resultado corroboram com os descritos por Alonso et al (2011), que verificaram correlação positiva entre a sorção do indaziflam e o conteúdo de carbono orgânico de diversos solos brasileiros.…”
Section: Indaziflamunclassified